Pengaruh Return On Equity, Current Asets Terhadap Firm Value Survei Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2012-2022 - Purnamasari, Dini; Kusmayadi, Dedi; Badruzaman, Jajang; Ansori, Ilman (POLITEKNIK LP3I, 2023)
The research aimed to analyze the influence of Return On Equity, Current Asets on firm value of food and beverage manufacturing companies wich resgistered in Indonesia stock exchange (idx) at 2012-2022 parrtialy.This research object cover the ROE,CR, and PBV. Data type used was secondary datas that was annual financial report from each industry which analyzed by Panel Data Regression. Result of thr research show that : Return On Equity has positive impact on firm value and Current Asets has negative effect on firm value.